Innovativeness as precondition for business excellence in public utiliy (communal) companies - Škafar, Branko (Organizacija (Kranj), 2008)
This article presents a new business excellence model for PUC (PUC), especially in countries in transition as one way to business excellence. The new model has proven successful in a multinational company's daughter company in Slovenia in practice as well as in comparison with companies performing the same activity. We are aware that there are no universal models for success, but there are tools which make it easier to reach. Of course, one single tool will not make a company successful. It must have a unique (original) and requisitely holistic business model to succeed. And talking about unique, i.e. different from others, brings us to innovativeness - the main topic of this research as the background of business excellence, including the PUC. The presented new model has been evolving over ten years and proved successful in practice.
Keywords: javna podjetja; komunalna podjetja; inovacije; inovativnost; poslovna uspešnost; poslovna odličnost